True triaxial physics simulations and process tests of hydraulic fracturing in the Da’anzhai section of the Sichuan Basin tight oil reservoir - Li, Song; Fan, Yu; Wang, Yang; Zhao, Yuanshou; Lv, Zefei; Ji, Zeng; Chen, Weihua; Min, Jian (Frontiers in Energy Research, 2023)
The limestone reservoir of the Da’anzhai section is the main production layer of Jurassic tight oil in central Sichuan, with tight and strongly heterogeneous reservoir rocks. In the early stages, small-scale plug removal and acidification techniques were mainly applied to the dacite section of the reservoir. However, using a single conversion method was not suitable for tight reservoirs with underdeveloped fractures. To address this challenge, we conducted large-scale real-world triaxial simulation test system experiments on hydraulic fracture propagation using samples from dense limestone outcrops. The aim was to elucidate the laws of hydraulic fracture propagation in dense limestone oil reservoirs. The L1 well in this area was selected to test the volumetric fracturing technology in order to achieve a breakthrough in test production and the reconstruction technology of the Da’anzhai section of the tight limestone reservoir. The experiments have shown that low stress differences, natural fracture development, and low viscosity slippery water are favorable factors for obtaining complex fracture morphology. In contrast to the construction parameters, the structural properties of the rock are the dominant factors in the formation of complex fracture morphologies. By optimizing the geological dessert and implementing targeted technological measures, bulk fracturing has been proven to be feasible for the dense limestone reservoir in the Da’anzhai section.